Mosaik Peradaban: Interaksi Manusia dan Kebudayaan - Taufik, Muhamad (Fakultas Seni Rupa dan Desain ITB, 2025)
The author in this book emphasizes that culture is an entity that continues to develop, starting from simple forms to reaching higher complexity. This development not only functions as a means of adaptation, but also as a way for humans to find solutions to the various challenges they face. More than that, culture is a reflection of the human way of life which is based on a system and symbols of values, which ultimately places humans in a transcendent reality.